The Differential Role of Cytokines on Stress Responses in a Menopause Rat Model - Park, Hyun Jung; Shim, Hyun Soo; Shim, Insop (Frontiers in Psychiatry, 2020)
Menopause is a risk factor of anxiety and depression. Also, psychoneurological symptoms are shown in almost all women in the perimenopausal period. The present study investigated if repeated stress modulates behavioral changes or balance of pro- and anti-inflammatory cytokine in ovariectomized (OVX) rats. The albino SD female rats were randomly divided into four groups: the naïve normal group (NOR), a surgically ovariectomized group (OVX), the only stressed group (ST), and OVX and stressed groups (OVX + ST). We performed a battery of tests such as the forced swimming test (FST), the sucrose intake and social exploration. In the same animals, corticosterone was assessed in the serum, and also, two representative cytokines (IL-1β and IL-4) were examined in different brain regions after all the behavior sessions for all the experimental groups. The OVX + ST group showed more immobility time in FST than the OVX group or ST group. Also, OVX + ST group was tended to decrease active social exploration and sucrose solution intake compared to the OVX group or ST group. The serum concentration of corticosterone of the OVX + ST group were higher than the OVX group or ST group and also the level of CORT in OVX +ST was markedly increased compared to the NOR group. In the brain, the number of IL-1β immunoreactive neurons of the OVX + ST group was increased compared to the NOR group. The OVX + ST group was tended to increase IL-1β positive neurons compared to OVX or ST group. However, the number of IL-4 immunoreactive neurons of the OVX + ST group was markedly decreased compared with the NOR group. Also, the IL-4 positive neurons in the OVX + ST group was significantly decreased when compared to the ST group. These results indicate that ovariectomy and stress combine to increase the depressive like behaviors and neuro-inflammatory responses. Together, these data show neuroinflammation as a potential contributor to depressive like symptoms during menopausal transition.